SUSTAINING LIFE WITH TREES: ECOCRITICISM PERSPECTIVE IN SELECTED PICTURE BOOKS - Tisnawijaya, Christy; Kurniati, Geni (Lire Journal (Journal of Linguistics and Literature), 2021)
The issue of the environmental problem has been prevalent especially in the contemporary era. The fact that Mother Earth is currently facing a lot of environmental concerns is the central discussion of the selected children’s picture books. Hence, this study aims to analyze how the picture books successfully capture the idea that trees are the symbol of Mother Earth per se. The selected picture books to be discussed are: A Tree is Nice by Janice May Udry (1984), The Giving Tree by Shel Silverstein (1992), Red Knit Cap Girl and The Reading Tree by Naoko Stoop (2014), Seasons Come, Seasons Go: Tree by Patricia Hegarty (2015) and The Tree by Neil Layton (2016). By scrutinizing the narrative and illustrative elements of the picture books, this study sheds light on how the ecosystems are held together by trees. The trees play a vital role in balancing and maintaining the world’s ecosystems. Moreover, the trees are valuable for providing environmental and social benefits. Hence, taking care of the trees can be perceived as maintaining a sustainable life for both the living and nonliving things. The underlying theories to support the discussion are those of ecocriticism, narrative and illustrative elements, and the trees as metaphor of Mother Earth, all of which are interconnected in children’s picture books.